Blogging in ESL class- gender-based attitude of the engineering students - Sahib Khatoon; Muhammad Jafre Zainol Abidin; Quratulain Mirza; Ashfaq Hussain (Institute of Advanced Engineering and Science, 2020)
Online learning has given a new context to the teaching and learning environment. This virtual environment changes the attitude of students in language learning. This study aimed to look into the difference among the engineering students' attitudes towards blogging in an ESL class in terms of gender and the effect of multimodal features on their reading attitude. The research method adopted in the present study relied on a qualitative approach. Engineering students from computer science engineering from local public engineering university Mehran University of Engineering and Technology Jamshoro (MUET) were taught English under blogging and were interviewed. Respondents’ attitude is mainly positive towards blogging. There were very few differences pointed out from their attitude towards blogging.